HUBUNGAN ANTARA WAKTU LAMA PUASA DENGAN KEJADIAN MUAL MUNTAH PADA PASIEN POST OPERASI DI RSUD PIRU KABUPATEN SERAM BAGIAN BARAT - Aloysius Timbu; Amin Zakaria; Widigdo Rekso Negoro; Suryanto Suryanto (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Introduction: Post Operative Nausea and Vomiting (PONV) is an unpleasant experience during the postoperative period at 24-48 hours, which is distressing for the patient and can prolong the length of stay, as well as increase the risk of postoperative complications. Fasting before surgery is necessary to minimize the risk of aspiration during anesthesia procedures. The aim of this study was to analyze the relationship between long periods of fasting and the incidence of nausea and vomiting in post-operative patients. Method: This type of research is correlation analysis with a cross-sectional design. The population of patients in the anesthesia unit who underwent caesarean section with SAB spinal anesthesia. The sample consisted of 64 consecutive sampling methods for the period April 2023. The independent variable was the duration of fasting and the dependent variable was the incidence of nausea and Vomiting was measured using an observation sheet, ratio data scale and data analysis using the one-way ANOVA correlation test with paired data. Results: The results of the hypothesis test of the relationship between the length of fasting and the incidence of nausea and vomiting in caesarean section patients with spinal anesthesia showed a significant value of 0.23, which means there is no relationship between the duration of fasting and the incidence. nausea and vomiting in patients due to post-operative nausea and vomiting with spinal anesthesia may be caused by other factors, namely: hypotension resulting in hypoperfusion, aerophagy, drug administration, surgical techniques (many manipulations of intestinal organs, and other factors. Conclusion: Suggestions for future researchers analyze the relationship between the incidence of nausea and vomiting on other factors or control confounding variables. Keywords: Length of Fasting, Post Operative Nausea and Vomiting